ACCRUAL BASED REGIME ADOPTION IN THE INDONESIAN PUBLIC SECTOR - Harun Harun (Jurnal Akuntansi Multiparadigma, 2010)
Abstract. Accrual Based Regime Adoption in The Indonesian Public Sector. A global trend indicates the emerging role of the private style reporting system as a part of New Public Financial Management reform in the public sector in developed and emerging economies. This study documents that the Indonesian goverments policy to formally adobt an accrual accounting reporting for the public sector in 2003 was part of wider public financial reform imposed by international donor communities and domestic aspiration as a means to strengthen the accountability, transparency and efficiency of public sector operation. Drawing from empirical data issued by the Goverment Institutions (e.g the State Audit Board) and the experience of a municipal goverment in implementing the new reporting system and other relevant information, the institutionalization of the new goverment reporting system in Indonesia has been encountered with a number critical issues: local goverments have been positioned as the passive adopter of the accounting regime against the decentralization policy, the low level of compliance to reporting standarts, the lack of using financial information for managerial purposes, and the emerge of an illegal practice as an unintended outcome of the public financial management reform. This paper concludes with practical recomendation and suggestion for future studies.